Learning peace (and conflict): the role of primary learning materials in peacebuilding in post-war Afghanistan, South Sudan and Sri Lanka. Issue 1 (2nd January 2017) - Vanner, Catherine; Akseer, Spogmai; Kovinthan, Thursica
Abstract: Post-war education is usually considered a positive contributor to peacebuilding; however, it can also reinforce divisive perspectives. Textbooks and learning materials can be instrumental in maintaining or exacerbating existing inequalities. This paper uses case study literature reviews of Afghanistan, South Sudan and Sri Lanka to explore the ways in which primary learning materials extend existing challenges of post-war education and potentially create new ones. An analysis of the literature on learning materials from these countries reveals that textbook development and uses are intertwined with larger national and international political and social power structures. We draw from Bourdieu and Giroux to consider how learning materials contribute to the reproduction of cultures of hostility, violence, divisiveness and silence or to transformatory cultures of peacebuilding, inclusivity and critical thought. Our resulting conceptual lens highlights how education can take on the role of being a victim, accomplice or transformer of conflict – roles that are often overlapping. Each case study country is taking steps towards peacebuilding through their primary learning materials; however, there are many elements of the textbook design, development, production and distribution process in each country that also reinforce contributing factors for conflict.